Digital Transformation of Public Safety Governance: The DKI Jakarta Satpol PP Enterprise Architecture Using TOGAF-ADM - Agus Supriadi Harahap; Andi Pitono; Muhadam Labolo (Bulletin of Social Studies and Community Development, 2026)
The rapid population growth in DKI Jakarta challenges the Civil Service Police Unit (Satpol PP) in maintaining public order, necessitating a robust management control system for its 5,500 field personnel. The existing operational application, SISAPPRA, operates sub-optimally due to misalignment with field procedures and isolated data structures. This study aims to analyze the Information and Communication Technology (ICT) requirements and design an enterprise architecture blueprint to enhance the operational management control system of Satpol PP DKI Jakarta. Employing a descriptive qualitative approach, data were gathered through direct observations of public order operations, in-depth interviews with three tiers of informants (leadership, IT staff, and field officers), and analysis of organizational documents. The data were systematically analyzed using the phases of The Open Group Architecture Framework Architecture Development Method (TOGAF-ADM). The gap analysis reveals critical functional deficiencies in the current application, including the absolute absence of access roles for command leadership, non-functioning spatial mapping features, and a lack of data integration with the Regional Civil Service Agency (BKD). To close these gaps, this study defines the target "SISAPPRA 2.0 Landscape," comprising 13 integrated modules and a 2024 implementation roadmap. The enterprise architecture successfully addressed blind spots in operational oversight by introducing a specialized investigation module for Civil Service Investigators (PPNS) and a dynamic executive dashboard. This research offers a theoretical novelty by integrating TOGAF-ADM with the Four Levers of Control concept, providing a transparent, command-integrated digital governance model tailored for high-risk public order enforcement. This enterprise architecture model can be adopted by Satpol PP agencies throughout Indonesia. Keywords: Enterprise Architecture, E-Government, Management Control System, Public Order Enforcement, TOGAF-ADM.